Einstellungen von Lehramtsstudierenden im Fach Mathematik : Erfahrungen und Perspektiven (mathematica didactica, 2003)
Different studies show rigid beliefs of teacher students concerning mathematics and teaching mathematics. These  beliefs can hardly be changed. However this is a special  task of teacher's education, if perspectives of mathematics instruction for the future are to be developed. Studies and experiences of my own  with teacher students for primary and first  secondary schools show steps to a development, particularly from which expectations of students can be started.